CTA Project Completion Report: Eyes in the Sky, Smart Techs on the Ground – Transforming Africa's Agriculture - Rambaldi, Giacomo (Technical Centre for Agricultural and Rural Cooperation, 2020)
By embodying components like scientific research, proof of concept initiatives, capacity building, support to investment, enterprise development, networking, experience capitalisation and communication, this action has started transforming Africa’s agriculture into a high-tech industry, with decisions being based on real-time gathering and processing of data, productivity and yields The establishment of 38 rapidly expanding, youth-led enterprises offering drone-based services in 21 African countries, represents a significant development for the continent and a milestone for the building of the African Information Society. Started at the end of 2016, this initiative caught the attention of young entrepreneurs who were selected via a competitive processes, trained, and technically and financially supported in offering drone-based services to farmers’ organisations, agribusinesses, government, international development agencies and other parties. A June 2019 survey confirmed that the enterprises have been recruiting staff, investing in new equipment, increasing their turnover and client portfolio. An industry association (Africa Goes Digital Inc. [AfGD]) has been established to support further growth of the enterprises and enable members to group, offer diverse services and be more competitive. The project played an important role in establishing an enabling environment for the technology. It supported the African Union’s appointed High-Level African Panel on Emerging Technologies (APET) in selecting drones for precision agriculture as one of the most promising technologies which would foster Africa’s development. In January 2018, the African Union (AU) Executive Council recommended that all Member States harness the opportunities offered by drones for agriculture. A full report entitled Drones on the horizon: Transforming Africa’s agriculture was launched at the Africa Innovation Summit in Kigali on 6 June 2018. Project implementers co-authored the report and have been advising national civil aviation authorities in developing regulations for the responsible use of drones. The project has been nominated as Champion and most importantly as winner in the category e-Agriculture of WSIS 2020.